Effect of WC addition on the microstructure and mechanical properties of TiN-based cermets. Issue 1 (January 2017) - Zeng, Wenmiao; Gan, Xueping; Li, Zhiyou; Zhou, Kechao
Abstract: The TiN–WC–Ni–Co system cermets with nearly full density were successfully fabricated by conventional vacuum sintering with the addition of WC. Effect of WC addition on the microstructure and mechanical properties of TiN-based cermets was studied in this work. The results showed that WC helped to improve the wettability significantly between TiN and Ni/Co through the formation of typical core-rim structure, which is rather beneficial to obtain the cermets with full densification and homogeneous microstructure. As the addition of WC content increased from 0 wt% to 25 wt%, the microstructure had a marked trend to become denser and finer and the mechanical properties of the TiN-based cermets were enhanced greatly. When the WC content was 20 wt%, the relative density, transverse rupture strength, fracture toughness and Rockwell hardness of the cermets reached 99.5%, 1235 MPa, 12.6 MPa m 1/2 and 88.2, respectively.